'What Determines Socio-Economic Status and What Reflects It?'—Partial Least Square-Structural Equation Modelling Approach. (July 2022) - Dey, Sumit; Upadhyay, Vandana; Chouhan, Manish
A pertinent question that remains unaddressed in literature is that 'what reflects socio-economic status (SES) and what determines it?' This is because in some studies income, education, consumption expenditure, health status etc. have been used as proxy indicators of SES, whereas, there are some other studies which consider these as the determinants of SES. In this context, this article has attempted to make a clear distinction between the determinants and indicators of SES. As a determinant of SES, we have certain factors, extensively used in literature and as an indicator of SES, Sen (1999) idea of freedom has been used. Partial least square-structural equation modelling has been applied to estimate our model.